Efektivitas Penerapan Blended Learning pada Masa Pandemi Covid 19 di Universitas Mathla’ul Anwar Banten - Sauri, Sopyan (Jurnal Artikula, 2021)
This study aims to determine the effectiveness of the application of blended learning during the Covid 19 pandemic. This research was conducted at Mathla'ul Anwar University Banten from September to November 2021. The research questions are as follows. (1) What learning model do you like the most? (2) Do you have difficulty in online learning. (3) When learning online what application do you like the most. (4) During this covid 19 pandemic, does the use of the blended learning model make you more enthusiastic in learning than online learning. (5) During this COVID-19 pandemic, does the use of the blended learning model make it easier for you to understand the material being taught than online learning. The research method used is descriptive qualitative research method. The technique of collecting data in this study was using a questionnaire instrument. The questionnaire was compiled using a google form. The research respondents were 77 students with random sampling technique.The results showed that 81.8% or 63 people chose face-to-face learning. The implementation of face-to-face learning for students is more focused on carrying out lectures because they are in places and conditions that are engineered and conducive. Then there are 76.6% or 59 students who agree that online learning is difficult to implement. This difficulty occurs because students are not used to doing online learning and the internet network is not stable. In addition, there are 61% or 47 students who choose the Google Meet application if learning is carried out online. The Google Meet application is the most chosen application because this application is the easiest to use than other applications. There are 74% or 57 students who agree that blended learning makes them more enthusiastic about learning. Students' enthusiasm for learning arises because in terms of material delivery, which is usually conventional with blended learning, the delivery of material is very diverse. And there are 67.5% agree that the application of blended learning will make students understand the material being taught faster than learning carried out online. this happens because when online learning the learning material is less understandable, when offline the material that is not understood can be discussed again so that it is more understandable.